العلاقات السردیة فی النص الشعري (قارئة الفنجان لنزار قباني) أنموذجا - محمد, أواز محمود (Sulaimani Journal for Humanities, 2025)
This research is attempting the connective narratives in the poem of (NizarQabbany)'s (Qariat al –Fingan).The method of working is named Narraitology Semantics which (Grimmas) depended on.Itcomprises the obligatory, permission and commitment connections.At the same time, it contains the kinds of narraitology wich emphasis on effects, suspicions, identifications, self–created and point of views which all should be done through the relative of sender, riceverand the message. All of them are the best reason for discovering the power of the contend and the form of the text with the expression of its writer.